Instalasi PLTS Sebagai Sumber Energi mandiri dan Media Pengajaran EBT Bagi Santri PPPI Al-Ittihad Malang - Nandang Mufti; Haidar Ali; Saparullah Saparullah; Nurul Lathii Fatul Chamidah; Retno Fitri Wulandari; Nur Asriyani; Ari Priharta; Nasikhudin Nasikhudin (Universitas Islam Malang, 2023)
Dependence on the need for electrical energy on PLN will undoubtedly require a high cost. Energy independence around the PPPI Al-Ittihad hut as a partner can minimize expenses and realize an Islamic life based on information technology and independence in energy. This problem has prompted the Malang State University community service team to install solar panels at PPPI Al-Ittihad based on smart PLTS that can be monitored in real-time. This installation serves as a source of electrical energy to meet the electricity needs of PPPI Al-Ittihad. Community service is carried out by observing, calculating load requirements, making designs, installing solar cell systems, and installing solar panel systems. The electricity generated by the smart PLTS is used for the daily needs of PPPI Al-Ittihad. Besides that, the PLTS could be the renewable energy learning media for students and IoT-based information technology. The installation of PLTS is very useful for PPPI Al-Ittihad, which has a daily power load of 4 kWh to reduce the estimated cost of electricity consumption which previously depended on PLN.